Penetration Enhancement of Topical Formulations - Keng Wooi Ng (MDPI AG, 2018)
This special issue, which is entitled “Penetration Enhancement of Topical Formulations”, presents a selection of the latest research that elucidates the challenges facing topical formulations for human skin in addition to proposing interesting solutions.[…]